Forestry in Travancore-cochin State - Iyppu, A. I. (Indian Forester, 1955)
The State of Travancore-Cochin having an extent of 9,144 square miles is blessed with vast resources of Forest wealth. The extent of the reserves alone come to 2,975 square miles. Artificial regeneration of teak is given top priority and teak plantations alone extend over 37,145 acres. Hardwood and softwood plantations cover an area of 7,406 acres. Natural regeneration of valuable species is quite satisfactory and the forest wealth is well protected. The gross yield of timber during the year 1952-53 was more than 33 Â½ lacs of cubic feet and the revenue realized is Rs. 181 lacs. Timber, firewood and reeds from the forests are supplied in large quantities to Firms like F.l.T., F.A.C.T., Government Plywood Factory and Punaloor Paper Mills, besides the supply of softwoods to various other private concerns. Sandal trees are also found in parts of the state forests in appreciable quantities and the Minor Forest Products are also important from the point of view of quality and quantity. Wild Game in its abundance are met with all over and capture and sale of elephants are a profitable and interesting work of the Forest Department. Recently attention has been paid for more scientific and technical aspects of starting a Silvicultural Division and working of forests under regular working plans. Proposals are ripe for starting a Soil Conservation Research Centre also.